High-density and targeted glycoproteomic profiling of serum proteins in pancreatic cancer and intraductal papillary mucinous neoplasm. (2nd December 2018) - Aronsson, Linus; Andersson, Roland; Bauden, Monika; Andersson, Bodil; Bygott, Thomas; Ansari, Daniel
Abstract: Objective: Glycoproteomics is an emerging subfield of proteomics. Tumor-specific variations in protein glycosylation might be potential targets for the development of new cancer diagnostics. Here, we performed high-throughput screening and targeted verification of glycome alterations in serum samples from patients with pancreatic cancer and the precancerous lesion intraductal papillary mucinous neoplasm (IPMN). Material and methods: The glycosylation profile of 1000 proteins was mapped in a discovery cohort comprising serum samples from 16 individuals, including 8 patients with pancreatic cancer and 8 healthy controls. The top 10 glycoprotein biomarker candidates with the highest signal intensity difference in glycosylation levels were evaluated in a cohort consisting of 109 serum samples, including 49 patients with resectable pancreatic cancer, 13 patients with resectable noninvasive IPMN and 47 healthy controls, using a targeted assay. Results: Multivariable analysis defined sets of panels comprising CA19-9 and distinctively glycosylated proteins for discrimination between pancreatic cancer, IPMN and healthy controls. A panel including CA 19-9, IL.17E, B7.1 and DR6 gave an AUC of 0.988 at 100% sensitivity at 90% specificity for the discrimination of stage 1 pancreatic cancer and healthy controls. B7.1 was found to be a valuable biomarker for differentiating between IPMN and healthy controls, with better performance alone than CA 19-9. Conclusions: Measurement of protein glycosylation profiles in serum may aid in the early detection of pancreatic cancer and precursor lesions.